A novel threat from invasive Lantana: stem exudate clogs the feet of small birds. (2nd January 2019) - Taylor, P. Barry; van Heerden, Fanie R.; Thompson, Lindy J.
ABSTRACT: A hard, black deposit was found clogging birds' feet at Ferncliffe Nature Reserve in South Africa. The reserve is infested with invasive Lantana ( Lantana camara ). We hypothesised that small frugivorous, nectarivorous and insectivorous birds which foraged in Lantana would be most affected by the hard deposit, which could enclose the toes, making the foot unusable. We investigated which bird species were affected by the hard deposit on their feet, and used liquid chromatography-mass spectrometry to compare samples of the deposit from the birds' feet to samples from young Lantana stems. White-bellied Sunbirds ( Cinnyris talatala ), Tawny-flanked Prinias ( Prinia subflava ) and Spectacled Weavers ( Ploceus ocularis ) were the three species whose feet were most affected with this deposit, and results confirmed that these deposits originated from exudate on young Lantana stems. This is the first time that Lantana stem secretions have been reported to adversely affect birds, but we believe the phenomenon may occur more widely in Lantana's native and invasive range.